Digital storytelling: a tool for promoting historical understanding among college students - Ericson H. Peñalba; Chaddlyn Rose C. Samaniego; Shiella Mae A. Romero (Association for Learning Technology, 2020)
As an engaging learning strategy, digital storytelling provides students opportunities for developing competencies as they immerse themselves in a meaningful learning experience. The study presented in this article explored the potential of digital storytelling as an instrument for the promotion of historical understanding. Thirty first-year teacher education students, who were divided into eight groups, participated in a digital storytelling project that required them to produce their own digital stories. The project was designed as an 8-week activity, which consisted of activities that guided them throughout the pre-production, production, and post-production phases. After the final week of the project, the students participated in focus group discussions. Aside from the focus group responses, data were also obtained from their reflection journal entries and digital stories. The qualitative data were subjected to thematic network analysis, surfacing six organising themes, namely historical significance, historical imagination, perspective taking, continuity, historical emphasis, and values and traits identification. These findings suggest specific courses of action for integrating technology in a history classroom.